Origin of High‐Frequency Radiation During Laboratory Earthquakes. Issue 7 (15th April 2019) - Marty, S.; Passelègue, F. X.; Aubry, J.; Bhat, H. S.; Schubnel, A.; Madariaga, R.
Abstract: We monitor dynamic rupture propagation during laboratory stick‐slip experiments performed on saw‐cut Westerly granite under upper crustal conditions (10–90 MPa). Spectral analysis of high‐frequency acoustic waveforms provided evidence that energy radiation is enhanced with stress conditions and rupture velocity. Using acoustic recordings band‐pass filtered to 400–800 kHz (7–14 mm wavelength) and high‐pass filtered above 800 kHz, we back projected high‐frequency energy generated during rupture propagation. Our results show that the high‐frequency radiation originates behind the rupture front during propagation and propagates at a speed close to that obtained by our rupture velocity inversion. From scaling arguments, we suggest that the origin of high‐frequency radiation lies in the fast dynamic stress‐drop in the breakdown zone together with off‐fault coseismic damage propagating behind the rupture tip. The application of the back‐projection method at the laboratory scale provides new ways to locally investigate physical mechanisms that control high‐frequency radiation. Plain Language Summary: Over geological time scales, partially or fully locked tectonic plates accumulate stress and strain. The stress and the strain build up on discontinuities that we call "faults." Natural faults exist either inside a tectonic plate or at the boundary between two distinct tectonic plates. When the stress accumulated on a fault exceeds the strength of the fault, the accumulated stress and strain, which can be interpreted in term of accumulated energy, are suddenly released. This natural phenomenon is called an "earthquake." During an earthquake, part of the energy is released in the form of seismic waves. Those seismic waves are responsible for the ground shaking. High‐frequency waves usually cause most of the damage. To better understand the physical parameters that influence the generation of high‐frequency waves, we experimentally reproduced microearthquakes and used them as a proxy to study real earthquakes. Our results showed that the higher the pressure acting on the fault when an earthquake is generated, the higher the amount of high‐frequency radiations. Moreover, our observations underlined that, during an earthquake, high‐frequency waves are released in specific areas on the fault. Thus, these results might be of relevance to improve seismic hazard assessment. Key Points: High‐frequency radiation is enhanced with both confining pressure and rupture velocity Acoustic sensors can be used as an array to track high‐frequency sources during rupture propagation High‐frequency radiation sources propagate consistently with the rupture front and are located behind it